Molecular Cloning and Expression Profile of Toll-Like Receptor 3 from an Indian Coldwater Fish, Schizothorax richardsonii(Gray). Issue 2 (3rd April 2017) - Belwal, Kiran; Thakuria, Dimpal; Dighe, Vikas; Pande, Veena; Pande, Amit
ABSTRACT: The innate immune system recognizes pathogens through pattern recognition receptors (PRRs), and toll-like receptors (TLRs) are one of the most important PRRs. TLR3 is a unique member of TLR family that recognizes double-stranded RNA (dsRNA), a viral replication intermediate. There is a variation in its response among diverse fish species toward the same stimulants. We identified and cloned TLR3 from Indian snow trout, Schizothorax richardsonii and carried out its expression analysis in un-induced and poly (I:C) challenged fish. It has an open reading frame (ORF) of 2712 bases that encodes a polypeptide of 904 amino acids. The molecular weight of the polypeptide was predicted to be 102.4482 kDa with an isoelectric point of 7.40. Quantitative real time PCR (qRT-PCR) was carried out after 24 hours of poly (I:C) treatment and expression of TLR3 was analyzed in different tissues. As compared with untreated fish the poly (I:C) challenged fish revealed significantly high expression of TLR3 in kidney followed by liver and gills.